Human diversity in education : - Cushner, Kenneth (The McGraw-Hill Companies, 2009)
This book is a research-based, comprehensive text designed to provide an introduction to multicultural education and diversity in society. It provides an updated and broad treatment of the various forms of human diversity found in todays schools including nationality, ethnicity, race, religion, gender, class, language, sexual orientation, and ability levels.